2012
DOI: 10.1002/app.38798
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and ionic conductive properties of all‐solid polymer electrolytes based on multiarm star block polymers

Abstract: A series of star block polymers with a hyperbranched core and 26 arms are successfully synthesized by atom transfer radical polymerization of styrene (St), and poly(ethylene glycol) methyl ether methacrylate from a hyperbranched polystyrene (HBPS) multifunctional initiator. All‐solid polymer electrolytes composed of these multiarm star polymers and lithium salts are prepared. The influences of polyoxyethylene (PEO) side‐chain length, PEO content, lithium salt concentration and type, and the structure of polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…different methods of preparation (solution–cast, melt compounding, ultrasonic assisted, microwave irradiated, ion irradiated methods, etc. ), addition of liquid plasticizers, dispersion of inorganic nanofillers, use of different salts, and their blending with other polymers . These studies revealed that the addition of plasticizers always increased the degree of salt dissociation and the amorphous phase of the SPE materials, which resulted in the increase of their ionic conductivity.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…different methods of preparation (solution–cast, melt compounding, ultrasonic assisted, microwave irradiated, ion irradiated methods, etc. ), addition of liquid plasticizers, dispersion of inorganic nanofillers, use of different salts, and their blending with other polymers . These studies revealed that the addition of plasticizers always increased the degree of salt dissociation and the amorphous phase of the SPE materials, which resulted in the increase of their ionic conductivity.…”
Section: Introductionmentioning
confidence: 96%
“…In the last one decade, the solid polymeric electrolytes (SPEs) have been a topic of great technological interests because of their uses in the high power and high energy density storage lithium‐ion batteries . These batteries are the promising power sources for the modern portable electronic equipments and the electrical vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…10 What's more, preparing multi-arm star-shaped copolymer with both rigid core and exible segment is another effective way to suppress crystallinity of SPE matrix, as well as to improve mechanical properties. [11][12][13] According to the pioneering work, star-shaped copolymers based SPEs usually show improved ambient conductivities ($10 À5 S cm À1 ). [11][12][13][14][15] As a bonus, the mechanical performance of the SPE lms can be improved signicantly by introducing the rigid component.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] According to the pioneering work, star-shaped copolymers based SPEs usually show improved ambient conductivities ($10 À5 S cm À1 ). [11][12][13][14][15] As a bonus, the mechanical performance of the SPE lms can be improved signicantly by introducing the rigid component. 12 Another widely studied polymer matrix for SPE is polyester, which has wide electrochemical window and high permittivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation